АSSЕSSING THЕ NЕЕD АND PОSSIBILITY ОF USING RЕCОMMЕNDЕR SYSTЕMS IN UNIVЕRSITY LIBRАRIЕS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Despite the growing number of scientific and technical information sources, traditional library search systems cannot fully meet the dynamically changing needs of users. Therefore, the implementation of personalized user-oriented services has become one of the main tasks of modern libraries. Recommender systems can be used in academic libraries not only to provide information resources that meet the interests and needs of users, but also to replenish the library collection with relevant sources of information. However, in practice, the creation of a recommender system for academic libraries requires taking into account the features of the library infrastructure and information resources, as well as its users. The purpose of the article is to analyze the need and possibilities of creating recommender systems in academic libraries based on the results of a survey conducted among the faculty and students of universities in Uzbekistan. Based on the results of the analysis, the authors developed recommendations for the creation of recommender systems in the context of the transformation of academic libraries in Uzbekistan. These recommendations can serve as important information for decision-making by university and library administrators, developers and researchers in this field who seek to improve user-oriented services in academic libraries.